Pengaruh Muhasabah terhadap Self Control di Fase Dewasa Awal (Studi Kasus pada Mahasiswa Angkatan 2017 Jurusan Tasawuf dan Psikoterapi UIN Sunan Gunung Djati Bandung) - Naufal Nurfajri Istiqomah; Cucu Setiawan; Firman Rismanto (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
AbstractHuman development is not limited to developing physically, but the development of a human being includes physical, psychological, responsibility and many others. A person will grow or develop starting from an early age covering the childhood phase, continuing to the adolescent phase, early adult phase, late adult phase and ending in the elderly phase. The early adult phase is a period of transition from the adolescent phase to the adult phase, in this phase a person is faced with adjusting to a new lifestyle by playing a new role. The need for muhasabah as a concept to deal with this new role by using the role of self-control as a way of controlling oneself in making a decision, attitude and assessment of something it faces. The purpose of this study is to examine the effect of reflection on the 2017 Sufism and Psychotherapy Class at UIN Bandung by explaining an overview of the reflections carried out, and explaining whether there is an effect on self-control in the early adult phase. This study uses a descriptive quantitative method approach using a questionnaire as a research tool and data collection, the data is processed using SPSS 26.0 and also data sources from the 2017 Sufism and Psychotherapy Class of 183 people taken 20% of the total population to 36 people. Based on the data that has been processed, the level of muhasabah and self-control in the early adult phase is in the medium category with a percentage of 62% for muhasabah and 70%. And the results of simple linear regression data analysis showed that the value of Sig. 0.830 means that there is no effect of muhasabah on self control in the early adult phase.